KEMAMPUAN PENALARAN MATEMATIS SISWA MODELDISCOVERY LEARNING DAN CONNECTED MATHEMATICS PROJECT - Hepi Laura Ebrianti; Masri Masri (Jurnal Math-UMB.EDU, 2019)
This study aims to: (1) find out the significant differences of students’ math reasoning abilities with the Discovery Learning model, Connected Mathematics Project (CMP) learning model, and conventional learning models; (2) find out which one of the above models are considered as the better model. This study was a quasi-experimental with the population from eighth grade students of SMPN 6 Bengkulu city and took sample from three classes namely VIII-D as the experimental class 1, class VIII-E as the experimental class 2, and class VIII-F as the control class.The technique for collecting data used a test of mathematics reasoning ability and analyzed by using one-way ANOVA test and continued with LSD test. Based on the result of study there were significat differences in students’ math reasoning abilities by using Discovery Learning, Connected Mathematics Project (CMP) and the conventional learning models.From the BNT test was obtained that Connected Mathematics Project (CMP) learning model gives the better results of students’ mathematics reasoning abilities than the Discovery Learning and Conventional learning models. Keywords: Reasoning Ability, Discovery Learning, CMP